Connecting with social and emotional well‐being in rural Australia: An evaluation of 'We‐Yarn', an Aboriginal gatekeeper suicide prevention workshop. (27th November 2020) - Davies, Kate; Read, Donna M. Y.; Booth, Angela; Turner, Nicole; Gottschall, Kristina; Perkins, David
Abstract: Objective: This evaluation considered the potential of We‐Yarn, a suicide prevention gatekeeper training workshop, to contribute to Aboriginal suicide prevention in rural New South Wales. Design: A mixed methods approach included surveys, in‐depth interviews and workshop observations. Setting: Aboriginal suicide prevention training in rural New South Wales, Australia. Participants: Attendees at We‐Yarn training. Intervention: We‐Yarn provided culturally safe suicide prevention skills training for Aboriginal people and for those who work with Aboriginal communities and persons in rural New South Wales. Training workshops were delivered across multiple locations for 6 hours in one day. Workshops were facilitated by two facilitators with lived and professional experience; one Aboriginal and one non‐Aboriginal facilitator. We‐Yarn content was developed by staff from the Centre for Rural and Remote Mental Health, and in consultation with Aboriginal Elders and representatives of Aboriginal Medical Services to ensure relevance and cultural appropriateness. Main outcome measures: Pre and post‐workshop surveys captured capacity and participants' confidence in identifying and responding to a person at risk of suicide. Interviews explored participants' experiences of workshops, implementation of learning, and attitudes regarding social and emotional wellbeing and suicide. Observations detailed the workshop environment, participants' engagement, and participants' responses to facilitators and content. Results: We‐Yarn was considered culturally appropriate. Participants responded to facilitators' lived experiences. Participants reported significant improvements in understanding the links between cultural strengths, social and emotional wellbeing and suicide prevention. However, health professionals with existing knowledge wanted a stronger focus on clinical training. Conclusion: We‐Yarn promoted discussion of suicide prevention within a holistic health framework, building on participants' pre‐existing knowledge about social and emotional wellbeing. Importantly, skilful facilitators with lived experience were vital to the success of the workshops. Consideration should be given to attracting people with low suicide prevention knowledge to the workshops, developing tailored workshops for health professionals and ensuring prolonged engagement with communities. Multifaceted and long term responses in addition to this type of training are important.